Good enough! Are socially responsible companies the more successful environmental innovators? - Christiane Reif; Sascha Rexhäuser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
The link between Corporate Social Responsibility (CSR) activities and financial performance of firms has been intensively examined and debated in academics and politics, but the connection to innovation has so far lacked research attention. This paper investigates whether CSR is complementary to environmental innovations, so that a joint introduction of both strategies generates a higher financial performance than the application of one or none of the strategies. We analyse if environmental innovators can generate higher financial performance by signalling their environmental engagement through CSR. For this purpose, we use panel data of environmental R&D activity together with a CSR variable on the Global Reporting Initiative (GRI) and analyse their effect on the financial performance of a firm. The novelty of our work is the complementary approach with which we examine the effect of a joint strategy of environmental R&D and CSR on financial performance. Although our results support the view of strategic complements for environmental R&D and GRI, we cannot conclude that this is also true for other types of CSR signalling environmental engagement.
urn:nbn:de:bsz:180-madoc-388473
Keywords: O32; Q56; 330; complementarity; environmental R&D; CSR; signalling; reputation; Global Reporting Initiative